Understanding Engagement with a Physical Health Service: A Qualitative Study of Patients with Severe Mental Illness. (December 2019) - Melamed, Osnat C.; Fernando, Indira; Soklaridis, Sophie; Hahn, Margaret K.; LeMessurier, Kirk W.; Taylor, Valerie H.
Objective: Individuals with severe mental illness (SMI) are disproportionally affected by medical comorbidities, resulting in poor physical health and premature death. Despite this, care for chronic medical conditions is suboptimal, and there is limited research that explores this phenomenon from the patient's perspective. The aim of this study was to identify barriers and facilitators of engagement with a physical health service experienced by individuals with SMI. Methods: Adults with SMI were recruited from a large psychiatric hospital and offered referral to a physical health service focused on the prevention and treatment of obesity and diabetes. Interviews were conducted at referral, 3, and 6 months. Data from 56 interviews of 24 participants were analyzed using the framework method to identify factors influencing engagement. Results: Barriers to engagement were identified at individual, medical program, and health system levels. Factors influencing the individual experience included difficulty in care coordination, affective symptomatology, and ability to bond with providers. Factors at the program level included difficulty adjusting to the clinic environment and the inability to achieve treatment goals. Factors at the system level included challenges in attending multiple appointments in a fragmented health system, lack of social support, and financial constraints. Conclusions: This qualitative study suggests that traditional models of medical care for chronic conditions pose challenges for many individuals with SMI and contribute to health disparities. Adaptation of medical care to populations with SMI and close collaboration between medical and mental health services are necessary to improve medical care and, subsequently, health outcomes.